2014
DOI: 10.1074/jbc.m114.579870
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-induced Disruption of Calcium Homeostasis Induces Endoplasmic Reticulum Stress in Macrophages

Abstract: Background:Macrophages are important cells in fibrotic diseases. Results: Chrysotile increases cytosolic calcium (Ca 2ϩ ) and induces endoplasmic reticulum (ER) stress in macrophages in a Ca 2ϩ -dependent manner. ER stress is found in alveolar macrophages from fibrotic lungs. Conclusion: Chrysotile triggers ER Ca 2ϩ leak and induces ER stress in macrophages. Significance: Macrophages undergo ER stress, which may contribute to pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Ox-LDL caused significant SR-A1 upregulation with concomitant activation of ERS as assessed by upregulation of GRP78. Ryan et al [85] also detected an increased level of ERS in macrophages. ERS induced by asbestos caused disruption of calcium homeostasis.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 89%
“…Ox-LDL caused significant SR-A1 upregulation with concomitant activation of ERS as assessed by upregulation of GRP78. Ryan et al [85] also detected an increased level of ERS in macrophages. ERS induced by asbestos caused disruption of calcium homeostasis.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 89%
“…Several factors linked with an increased likelihood of pulmonary fibrosis, e.g. viral infection, asbestos, amiodarone and old age, each activate the UPR in the lung, which is consistent with a potential role for ER stress in the pathogenesis of pulmonary fibrosis [10][11][12][13][14]60]. However, the link between ER stress and interstitial lung disease appears to be complex.…”
Section: Pulmonary Fibrosismentioning
confidence: 92%
“…Asbestos-induced ER-Ca 2+ release and proapoptotic ER stress in AECII could also be prevented by overexpression of the antiapoptotic protein Bcl-X L , but not with the chemical chaperone 4-PBA [226]. Similarly, Ryan and coworkers observed rapid and sustained increases in cytosolic Ca 2+ -levels in macrophagelike THP-1 cell lines in response to crysotile-exposure, with concomitant activation of ATF6α-and XBP1-pathways [228]. Anisomycin, an inhibitor of translocon Ca 2+ leak, inhibited induction of ER stress markers suggesting that ER Ca 2+ depletion may be the major cause of ER stressactivation in macrophages exposed to chrysotile [228].…”
Section: Er Stress In Drug-induced Interstitial Lung Disease (Ild)mentioning
confidence: 88%
“…Of note, no significant apoptosis was observed in macrophages of chrysotile-exposed C57Bl/6 mice, and active TGF-β levels were increased in BALF of such mice. The authors then concluded, that bronchoalveolar macrophages undergo adaptive/protective ER stress for cell survival in response to chrysotile exposure, and that this is an important contributory factor for development of asbestos-induced lung fibrosis [228]. However, the authors did not analyse by means of immunohistochemistry the expression patterns of ER stress-markers in fibrotic lungs of chrysotile exposured mice, and the putative involvement of AECII in disease pathogenesis was also not addressed in this study [228].…”
Section: Er Stress In Drug-induced Interstitial Lung Disease (Ild)mentioning
confidence: 90%
See 1 more Smart Citation